Ressignificação da escola: a circulação da ideologia - Baccega, Maria Aparecida (Comunicação & Educação, 1999)
This article proposes ideology matters should be added to the many aspects that are being and that are yet to be discussed concerning giving School new meaning. It shows ideology as a social praxis, a prescribing set of representations and norms, that find a privileged place in the symbolic forms that circle all over the world, through, most of all, the media. The article points to ideology and meaning construction, ideology and day-to-day living, to the circulation of symbolic forms and the media, and to ideology as a possible script for thematic discussion.